E-Module Contextual Approach to the Content of Science Subjects for Grade IV Elementary School Students - Ni Kadek Epa Listiana; I Komang Sudarma; I Made Tegeh (Jurnal Media dan Teknologi Pendidikan, 2025)
Students often experience difficulties in understanding abstract concepts due to the lack of connection between the learning material and real-life situations. This condition leads to low learning motivation and poor academic achievement, particularly in the subject of Science and Social Studies (IPAS). This development research aims to analyze the effectiveness of a contextual-based e-module in IPAS learning for fourth-grade elementary school students. The development model used in this study is the Hannafin and Peck model. Data were collected through tests, questionnaires, and interviews. The data analysis techniques employed include descriptive quantitative analysis, qualitative analysis, and inferential statistical analysis using a t-test. The research subjects included content experts, instructional design experts, instructional media experts, three students for individual trials, nine students for small group trials, and 25 fourth-grade students for field testing. The results indicated that the developed e-module had a very high level of validity based on expert evaluations, covering content, design, and media aspects, and were supported by positive responses from students. In addition to being valid, the e-module was also proven effective in improving students’ learning outcomes. This was demonstrated by the results of the t-test, which showed a significant difference between the pretest and posttest scores. The average pretest score of 46 increased to 81 in the posttest, with a tvalue of 17.356, which exceeded the ttable value of 2.010. Based on these findings, it can be concluded that the contextual-based IPAS e-module is effective in enhancing students’ understanding and learning outcomes in fourth-grade elementary education.